New technologies and their input into the maritime balance in the Asia-Pacific region - McCoffrei, Jack (Kuala Lumpur : MIMA, 1995)
This issue paper was presented by Capt. Jack McCoffrie RAN, Maritime Studies Programme, at the Joint Workshop on Regional Maritime Cooperation and Sea-Borne Trade, Kuala Lumpur, 7th & 8th December 1994
Keywords: Maritime law; Military technology